Peran kepadatan kerang hijau dalam meningkatkan pertumbuhan dan karakteristik sel gracilaria verrucosa pada sistem polikultur - Afifah, Della Nur; Rahim, Andi Rahmad (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2025)
Polyculture is a system wherein diverse organisms cohabit to mutually sustain one another. Green mussels (Perna viridis) are filter feeders that enhance water quality and facilitate the proliferation of other creatures. This study looks at how the number of green mussels affects the Total Organic Matter (TOM) content, cell count, cell features, and the absolute weight growth of Gracilaria verrucosa in a polyculture system in the pond at Pangkahkulon village. We evaluated three density treatments of green mussels (10, 20, and 30 individuals/m2) over a duration of 21 days. TOn the first day, the results showed a variation in TOM concentrations from 86.71 to 86.91 mg/L across all treatments; however, by day 21, there was a notable decline, with the 30 individuals/m2 treatment dropping to 33.18 mg/L. he cell count of Gracilaria verrucosa fluctuated, with the 30 individuals/m2 density treatment yielding the maximum count of 82 cells, followed by the 20 individuals/m2 treatment. Analysis of Variance (ANOVA) and Tukey's post hoc test showed that green mussel density had a big effect on the seaweed's absolute weight growth, even though there were no significant changes in cell count. These findings indicate that green mussels can enhance water quality and facilitate the proliferation of seaweed in polyculture systems.